PREFERENSI HAMA KEPINDING TANAH (Scotinophara coartata F) PADA BEBERAPA VARIETAS TANAMAN PADI SAWAH - Moonik, Jandrio H.; Manueke, J.; Tarore, D. (Universitas Sam Ratulangi, 2017)
ABSTRACTÂ Rice Black Bug (Scotinophara coartata F) is one of the most important pests that attack rice crops and has caused major losses. The purpose of this study is to determine the Rice Black Bug preferences in some varieties of rice crops. This research was conducted in Modomang Village, East Dumoga Subdistrict of Bolaang Mongondow Regency from November 2016 - February 2017. This research used Completely Randomized Design (CRD) with 5 treatments, namely several varieties of rice field cultivation (Ciherang, Cigeulis, Membramo, Pertiwi and Serayu).Based on the results of this study showed that the population of S. coartata pest with the largest average in Serayu varieties of 6 tails, followed by Membramo 3.75 tail, 3.5 Pertiwi, 3.5 Cigeulis and the lowest Ciherang with an average of 3.25 tailKeywords: preferences, rice black bug pest, varieties plants rice